Q. 6

# Prove that [Hint: Express L.H.S.

To prove:

As equation on RHS is a simplified expression, so we must opt Left side equation and simplify it further so that we can get

LHS = RHS.

And thus we will be able to prove it.

LHS =

By seeing the expression we can think that the problem can be solved using transformation formula:

By transformation formula, we have:

2 cos A cos B = cos(A + B) + cos (A – B)

-2 sin A sin B = cos(A + B) - cos (A – B)

Or cos A – cos B =

But as LHS expression does not contain ‘2’ in its term. So we multiply and divide the expression by 2.

LHS =

Applying transformation formula, we have –

LHS =

LHS =

LHS = { cos (-x) = cos x}

LHS =

Again, applying the transformation formula:

LHS =

LHS =

LHS = sin 4θ sin = RHS

Hence:

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Trigonometric Functions - 0152 mins
Conditional Identities31 mins
Trigonometric Functions - 0568 mins
Trigonometric Functions - 0366 mins
Trigonometric Functions - 0658 mins
Trigonometric Series45 mins
Interactive Quiz on trigonometric ratios & identities73 mins
Trigonometric Functions - 0268 mins
Trigonometric Functions - 0466 mins
Trigonometric Functions - 0865 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

Prove that:

RD Sharma - Mathematics

Prove that:

RD Sharma - Mathematics

Prove that :

RD Sharma - Mathematics

Prove that:

RD Sharma - Mathematics

Prove that:

RD Sharma - Mathematics

Prove that:

RD Sharma - Mathematics

Prove that:

RD Sharma - Mathematics

Prove that:

RD Sharma - Mathematics